Impact of Green Marketing to Food and Beverages on Purchasing Decisions and Brand Image as a Mediation Variable (Case Study: Millennial Consumers) - Ajeng Uswatun Hasanah; Fitria Dina Riana; Hery Toiba (HABITAT, 2023)
The emergence of various threats to the environment, encourages companies to be able to apply a new business concept, namely by implementing issues related to marketing that apply the concept green marketing. Green marketing is the consistency of all activities designed to meet human needs and desires without harming the environment and not harming other living things. This study uses a quantitative approach which is analyzed by using statistical methods by Smart-PLS. Based on the results of the analysis that has been done, it can be seen by consumer perceptions about companies that apply the green marketing concept have good results. The variables in this study include green marketing and brand image as mediating variables which have positive and significant results on purchasing decision variables. Strategies that can be implemented are not using formaldehyde and hazardous chemicals (X1.2), providing a place for inventory storage close to the store (X2.2), providing the latest information on environmental issues (X3.2), holding seminars, and carrying out disaster care actions (X4.2) and collaborating with chemistry students regarding the products used originating from safe materials (X5.2).